2002
DOI: 10.1002/jnr.10153
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor‐2 converts PACAP growth action on embryonic hindbrain precursors from stimulation to inhibition

Abstract: Pituitary adenylyl cyclase activating peptide (PACAP) has been shown either to stimulate or to inhibit neural cell proliferation depending on the origin of the cell population. We show here that, depending on the presence or absence of fibroblast growth factor-2 (FGF-2, also called basic FGF), PACAP may either stimulate or inhibit DNA synthesis in neural precursors isolated from embryonic day 10.5 mouse hindbrain. In the absence of FGF-2, PACAP stimulated 3H-thymidine incorporation in a dose-dependent manner. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…VPAC 1 and/or VPAC 2 genes also appear to be expressed in several germinal regions of the developing nervous system, but generally at levels considerably lower than that of PAC 1 . In mouse E10.5 hindbrain, VPAC 1 and VPAC 2 mRNAs were below the level of detection by in situ hybridization, but were detected in RNA extracts from this region by RT-PCR [29]. In the rat, VPAC 1 gene transcripts were detected at low levels in germinal zones by in situ hybridization, and in derived cultures by RT-PCR [27].…”
Section: Embryonic and Early Postnatal Expression Of Pacap And Pacap mentioning
confidence: 98%
See 1 more Smart Citation
“…VPAC 1 and/or VPAC 2 genes also appear to be expressed in several germinal regions of the developing nervous system, but generally at levels considerably lower than that of PAC 1 . In mouse E10.5 hindbrain, VPAC 1 and VPAC 2 mRNAs were below the level of detection by in situ hybridization, but were detected in RNA extracts from this region by RT-PCR [29]. In the rat, VPAC 1 gene transcripts were detected at low levels in germinal zones by in situ hybridization, and in derived cultures by RT-PCR [27].…”
Section: Embryonic and Early Postnatal Expression Of Pacap And Pacap mentioning
confidence: 98%
“…Effects of VIP in these cultures included increased neuroblast mitosis, enhanced survival of both dividing and nondividing cells, and increased neurite outgrowth [47,48]. Interestingly, the survival effect of VIP was significantly lower in cultures obtained from later-stage embryos or from postnatal animals, whereas the [31][32][33] increased decreased increased trkB, BDNF Hindbrain neuroblasts [20,29] dual action 2 Cerebellar granule neurons [34][35][36][37][38] increased increased increased Olfactory neuron precursors [39] increased increased Sensory neurons [40] increased increased Motor neurons [41] increased Midbrain dopamine neurons [42] increased Forebrain cholinergic neurons [43] increased Oligodendrocyte precursors [28] increased Astrocytes [44,45] increased interleukin-6 Microglia [46] TNF· BDNF = Brain-derived neurotrophic factor; TNF· = tumor necrosis factor ·.…”
Section: E155 Rat Sympathetic Neuroblastsmentioning
confidence: 99%
“…Brains were removed, and cortex and underlying white matter immediately adjacent to the normal site of excitotoxin injection (see above) were rapidly dissected from the different animals for RNA extraction. Total RNA was extracted as described previously (Lelievre et al, 2002), followed by DNaseI. For each sample, 600 ng were used in reverse transcription (iScript kit; Bio-Rad, Hercules, CA).…”
Section: Real-time Reverse Transcription-pcr For Glucocorticoid Recepmentioning
confidence: 99%
“…To date, most studies of PACAP in the cerebellum have indicated that it increases proliferation of GCPs and promotes survival in the presence of various death-inducing stimuli (Vaudry et al, 1999(Vaudry et al, ,2002Tabuchi et al, 2001). On the other hand, recent studies of neurons in the embryonic cortex and hindbrain indicate that PACAP can inhibit proliferation of those cells (Suh et al, 2001;Lelievre et al, 2002). Thus, PACAP might contribute to cell-cycle exit in the cerebellum as well.…”
Section: Granule Cell-cycle Exit and Differentiationmentioning
confidence: 99%